Puisi Sufistik Jalaludin Rumi Tentang Makna Kematian (Analisis Psikoanalisis Jacques Lacan Pada Makna Kematian) - A Zahid (Spiritualita, 2019)
The Sufistic poem Jalaludin Rumi signals the living creature that death is a real entity. However, death is illustrated as a pleasant experience for believers, a last resort to the creator. Death is not frightening, but "death" is a symbolic message of desire in the next life by improving our attitudes and behavior. While in the poetry of Rumi the discourse of "Death" has a double dimension: in psychoanalysis the dimension of self (self) which performs self-identification becomes a passive-narcissistic desire, and in ethical-social discourse becomes a social self (collective subject), but the latter never happens because the real never identifies: free subjects never materialize. In the real world, the subject's desires are not satisfied. The meaning of death is always symbolized in the form of "burial" so that humans are defined if death is something scary.